Nuclear Magnetic Resonance-Based Metabolomics Approach to Evaluate the Prevention Effect of Camellia nitidissima Chi on Colitis-Associated Carcinogenesis - Li, Ming-Hui; Du, Hong-Zhi; Kong, Gui-Ju; Liu, Li-Bao; Li, Xin-Xin; Lin, Sen-Sen; Jia, Ai-Qun; Yuan, Sheng-Tao; Sun, Li; Wang, Jun-Song (Frontiers in Pharmacology, 2017)
Colorectal cancer (CRC) is one of the most common malignant tumors worldwide, occurring in the colon or rectum portion of large intestine. With marked antioxidant, anti-inflammation and anti-tumor activities, Camellia nitidissima Chi has been used as an effective treatment of cancer. The azoxymethane/dextran sodium sulfate (AOM/DSS) induced CRC mice model was established and the prevention effect of Camellia nitidissima Chi extracts on the evolving of CRC was evaluated by examination of neoplastic lesions, histopathological inspection, serum biochemistry analysis, combined with nuclear magnetic resonance (NMR)-based metabolomics and correlation network analysis. Camellia nitidissima Chi extracts could significantly inhibit AOM/DSS induced CRC, relieve the colonic pathology of inflammation and ameliorate the serum biochemistry, and could signiﬁcantly reverse the disturbed metabolic profiling towards the normal state. Moreover, the butanol fraction showed a better efficacy than the water-soluble fraction of Camellia nitidissima Chi. Further development of Camellia nitidissima Chi extracts as a potent CRC inhibitor was warranted.